Boundary re-assessment of the Meter Reading Unit (MRU) for Tenaga Nasional Berhad, TNB Cheras - Alia Syafika Zulkflee, 1995- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2019